Plant Competition Across Topographic Gradients in Neotropical Cerrado Savannas: An Isotopic Approach - Rossatto, Davi R. [UNESP]; Franco, Augusto C. (Springer Nature, 2023)
The Cerrado is the second most extensive biome in South America, encompassing a series of plant physiognomies, which normally form gradients of tree cover in the landscape from grasslands with no or little tree cover, through savannas of variable tree density to closed-canopy forests. It is mostly found in the Brazilian territory (from 2° N to 23° S) under a great diversity of climate, soils, and reliefs, showing a mosaic pattern of distribution at, both, landscape and local scales (Ratter et al. 1997). At local scales, different environmental factors can determine the occurrence of the different vegetation types (fire, soils, drought, and herbivory); however, the most elusive example of variations in the abundance of trees and ground layer species is the changes in vegetation structure along topographic gradients of a few hundred meters in the core region of the Cerrado (Eiten 1972). These changes are associated with decreases in species richness, changes on composition, and density of the upper canopy layer from the top to bottom of the topographic gradient, where the ground layer vegetation predominates. Historically, these changes in vegetation structure and composition were thought to be the result of plant competition and variations in edaphic factors (Goodland and Pollard 1973). In this chapter, we present the Cerrado and its vegetation gradients, the use of isotopes on plant ecology, and discuss the causes of such drastic variation on plant physiognomies using an isotopic approach (δ18O and δ2H), to provide new insights on how plant competition aligned with water table level and soil depth caused such structural variations. We show that soil depth, groundwater, water table level, and depth of root water extraction interact on determining the ability of plants to successfully compete under different parts of topographic gradients. At the top of the gradient, soils are deep, with deeper water table, which allows plants with different root depths to thrive, potentially minimizing the effects of belowground competition. At the bottom of the topographic gradient, restricted soil depth and a shallow water table, that remains near or at the soil surface, normally during the wet season, promotes the selection of shallow rooted plants, eliminating woody species with deeper roots or species sensitive to waterlogging.